Magnetic field sensors based on undoped In0.53Ga0.47As/InP heterostructures fabricated by molecular beam epitaxy and metalorganic chemical vapor deposition - Przesławski, Tomasz; Wolkenberg, Andrzej; Kaniewski, Janusz; Regiński, Kazimierz; Jasik, Agata (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In this paper we, describe the design and fabrication process of Hall and magnetoresistor cross-shaped sensors using In0.53Ga0.47As/InP layer structures as active media. The influence of geometric correction factor GH on sensitivity parameters of these devices has been investigated. The results have been used in order to optimize the structure design behavior at temperatures ranging from 3 to 300 K. The large changes of the galvanomagnetic parameters vs. magnetic field and temperature allow these devices to be used as signal and measurement magnetic field sensors.
Optica Applicata, Vol. 35, 2005, nr 3, s. 627-634
Keywords: optyka; Hall sensors; magnetoresistors; InGaAs/InP heterostructures; electronic transport; geometric correction factor; molecular beam epitaxy (MBE); metalorganic chemical vapor deposition (MOCVD)